PENGARUH PENYALURAN KREDIT DAN KREDIT BERMASALAH TERHADAP LABA PADA KOPERASI UTAMA ARTHA JAYA CABANG SEMPIDI PERIODE 2013-2017 - Ni Ketut Dewi Mustikayani (Majalah Ilmiah Widyacakra, 2019)
The Title Research is The Influence of Credit and Problem Loans on Profit at Koperasi Utama Artha Jaya Cabang Sempidi for the period 2013-2017. The activity of giving credit to cooperatives is very important, the large amount of credit channeled can determine the benefits obtained. However, not all credits distributed will provide large profits and vice versa. Therefore it is necessary to emphasize risk. The risk posed by credit activities carried out by cooperatives is one of them is problem loans. If the number of problem loans increases, it will directly affect the decrease in profits that will be obtained by financial institutions. This research aimed to analyze the influence of Credit and problem loans on Profit at Koperasi Utama Artha Jaya Cabang Sempidi for the period 2013-2017. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method and documentation study. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the Credit and problem loans on Profit at Koperasi Utama Artha Jaya Cabang Sempidi is the credit variable (X1) partially and significantly positive influenced on profit (Y) with value of t-test is 6,388 and sig. 0,024 and problem loans variable (X2) significantly negative influenced on profit variable (Y) with value of t-test is -5.120 and sig. 0,036 at Koperasi Utama Artha Jaya Cabang Sempidi.